South Korean Capital Market Reacts to Park Ji Min's Solo Debut - Ahsta, Wahyu Farah Fathin; Sutisman, Entar; Kartim, Kartim (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study analyzes the South Korean stock market reaction to HYBE stock before and after Park Ji Min's solo debut on March 24, 2023. Research Design and Methodology: The analytical techniques employed are the paired sample t-test for normally distributed data, the Wilcoxon signed-rank test for non-normally distributed data, and the single index model technique for beta risk variables. Findings and Discussion: The results showed significant differences in abnormal returns, stock prices, and beta risk of HYBE shares before and after Park Ji Min's solo debut. Implications: This research makes a unique contribution to the accounting and financial management field by providing insights into international investment and its relation to signaling theory and event study. It can significantly advance our understanding in these areas and pave the way for further research.